Assessing farmland suitability for agricultural machinery in land consolidation schemes in hilly terrain in China: A machine learning approach - Yang, Heng; Ma, Wenqiu; Liu, Tongxin; Li, Wenqing (Frontiers in Plant Science, 2023)
Identifying available farmland suitable for agricultural machinery is believed to be the most promising way of optimizing agricultural production and increasing agricultural mechanization. Consequently, farmland consolidation suitable for agricultural machinery (FCAM) is implemented as an effective tool for increasing sustainable production and mechanized agriculture. This paper assessed the suitability of farmland for agricultural machinery in land consolidation schemes based on four parameters, i.e., natural resource endowment, accessibility of agricultural machinery, socioeconomic level, and ecological limitations. The weights for the factors were assigned based on the machine learning approach. The results showed that most of the farmland (76.41%) was basically and moderately suitable for the FCAM. Although slope was often a favourable indicator for the suitable land for agricultural machinery, the inferior accessibility of tract roads, continuous depopulation, and ecological fragility were unsuitable for the FCAM, which contributed greatly to reducing the overall suitability. Moreover, it was estimated that 720.8 kg/ha of the potential productivity of farmland would be increased if the FCAM were implemented. We carried out zoning according to the importance of the “suitability” and “improvement potential of farmland productivity”, and four zones were obtained as a result, i.e., priority consolidation zone, moderate consolidation zone, comprehensive consolidation zone, and reserve consolidation zone. More importantly, this zoning has been an effective solution for implementing FCAM schemes. Namely, the four zones constituted a useful basis for the implementation sequence and differentiated strategies for FCAM schemes. Apart from this, it was necessary to adopt some alternative strategies, such as strengthening farmland ecosystem protection, promoting the R&D of agricultural machinery suitable for hilly terrain, and increasing financial support, which may contribute to the feasible implementation of FCAM schemes and the achievement of modern and sustainable agriculture.